2008
DOI: 10.1016/j.jtcvs.2007.10.006
|View full text |Cite
|
Sign up to set email alerts
|

On-pump beating-heart coronary artery bypass grafting after acute myocardial infarction has lower mortality and morbidity

Abstract: On-pump beating-heart coronary artery bypass grafting is the preferred method of emergency myocardial revascularization for patients with acute myocardial infarction who might tolerate cardioplegic arrest poorly. It has lower postoperative mortality and morbidity than conventional coronary artery bypass grafting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
66
0
4

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(72 citation statements)
references
References 28 publications
2
66
0
4
Order By: Relevance
“…The early mortality rate of CABG for AMI is reported to be between 8.2% and 42.6%. [2][3][4][5][6][7] In addition, many patients show delayed cardiac events and cardiac death. In the SHOCK trial for AMI patients with cardiogenic shock, White et al reported that patients treated with CABG had a greater prevalence of diabetes and more severe coronary disease than did those treated with PCI.…”
Section: Introductionmentioning
confidence: 99%
“…The early mortality rate of CABG for AMI is reported to be between 8.2% and 42.6%. [2][3][4][5][6][7] In addition, many patients show delayed cardiac events and cardiac death. In the SHOCK trial for AMI patients with cardiogenic shock, White et al reported that patients treated with CABG had a greater prevalence of diabetes and more severe coronary disease than did those treated with PCI.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a novel hybrid procedure of beating heart surgery with the use of CPB to support the systemic circulation but without CA has been used in an increasing number of centres to treat high-risk patients with either poor left ventricular function or recent myocardial infarction [13][14][15][16][17]. Yet, to date, very little data exist as part of a clinical trial to validate this surgical approach.…”
Section: Introductionmentioning
confidence: 99%
“…As such, the authors hypothesized that the on-pump beating heart approach eliminates intraoperative global myocardial ischemia compared to the arrested heart that depends on cardioplegia for myocardial protection. In 2008, Miyahara and colleagues compared conventional CABG to PAD-CAB in acute MI patients [11]. The hospital mortality in the PAD-CAB group was superior to the traditional CABG group (2.6% vs. 21.7%) with two additional findings-more patients needed IABP support in the conventional CABG group following revascularization and fewer patients developed post-operative renal insufficiency in the PAD-CAB group.…”
Section: Discussionmentioning
confidence: 99%